Counseling on Stunting Prevention by Increasing Local Food Security Leads to the Climate Village Program - Yulianti, Ika; Ariyanti, Ririn; Lewuk, Maria Ulfanti Uhle; Noviani, Doris; Hidaya, Nurman (Fakultas Ilmu Kesehatan Universitas Borneo Tarakan, 2024)
Stunting is a growth disorder that generally occurs in children under five and the cases are increasingly worrying. Based on the results of the survey, the stunting rate in Nunukan Regency is the highest in North Kalimantan. Until now, the number of stunting cases in Nunukan has reached 1,101 children under five and spread across 21 villages. And one of the villages affected by stunting is Srinanti Village, Seimanggaris District. Seimanggaris can take advantage of the climatic village area where the strategy to be applied is in the form of planting tarp trees (Artocarpus odoratissimus) which have various health benefits and also a form of savings to increase the supply of tarap seed raw materials in the future for the processing of Sutarma innovation